2015
DOI: 10.3389/fpsyg.2015.01053
|View full text |Cite
|
Sign up to set email alerts
|

Belief in school meritocracy as a system-justifying tool for low status students

Abstract: The belief that, in school, success only depends on will and hard work is widespread in Western societies despite evidence showing that several factors other than merit explain school success, including group belonging (e.g., social class, gender). In the present paper, we argue that because merit is the only track for low status students to reach upward mobility, Belief in School Meritocracy (BSM) is a particularly useful system-justifying tool to help them perceive their place in society as being deserved. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…Endorsing a status system as fair allows the subjectively lower classes to hope that the system will permit them to achieve a higher social status in the future (Owuamalam et al., ; cf. Wiederkehr, Bonnot, Krauth‐Gruber, & Darnon, ). The more one believes that a status system is fair, the more one can hope that the system will allow changes that improve one's group outcomes in the future.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…Endorsing a status system as fair allows the subjectively lower classes to hope that the system will permit them to achieve a higher social status in the future (Owuamalam et al., ; cf. Wiederkehr, Bonnot, Krauth‐Gruber, & Darnon, ). The more one believes that a status system is fair, the more one can hope that the system will allow changes that improve one's group outcomes in the future.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…In modern society, meritocracy has allowed low status group members to dream about improving their social status, economic class, and place in the hierarchy, implanting the ideology that everyone has a chance of succeeding if they cultivate the required abilities (Wiederkehr et al, 2015). In this vein, meritocracy has served as an engine of meritocratic upward mobility for maintaining social order and calming social unrest.…”
Section: Meritocracy As a Social Systemmentioning
confidence: 99%
“…There is, ironically, a strong belief that success is a valid indicator of personal effort and performance (Wiederkehr et al, 2015). From this point of view, the idea of meritocracy as an ideology and a system in which rewards are impartially distributed according to individual talent has gained support from people at the bottom of the social ladder in a given society (Chong, 2014;Newman et al, 2015).…”
Section: Concepts Of Meritocracymentioning
confidence: 99%
See 1 more Smart Citation
“…Curtin, 2011;Rubin & Wright, 2015;Soria, Stebleton, & Huesman, 2013;Wiederkher, Bonnot, Krauth-Gruber, & Darnon, 2015). As Keefer, Goode, and Berkel (2015) found the relevance of the class consciousness in the social and political psychology literature, it is shown that the current use of subjective measure misses some important picture about social class.…”
mentioning
confidence: 99%